The development of the Be Active & Relax "Vitality in Practice" (VIP) project and design of an RCT to reduce the need for recovery in office employees - Coffeng Jennifer K; Hendriksen Ingrid JM; Duijts Saskia F; Proper Karin I; van Mechelen Willem; Boot Cécile RL (BMC, 2012)
Abstract Background There is strong evidence to suggest that multiple work-related health problems are preceded by a higher need for recovery. Physical activity and relaxation are helpful in decreasing the need for recovery. This article aims to describe (1) the development and (2) the design of the evaluation of a daily physical activity and relaxation intervention to reduce the need for recovery in office employees. Methods/Design The study population will consist of employees of a Dutch financial service provider. The intervention was systematically developed, based on parts of the Intervention Mapping (IM) protocol. Assessment of employees needs was done by combining results of face-to-face interviews, a questionnaire and focus group interviews. A set of theoretical methods and practical strategies were selected which resulted in an intervention program consisting of Group Motivational Interviewing (GMI) supported by a social media platform, and environmental modifications. The Be Active & Relax program will be evaluated in a modified 2 X 2 factorial design. The environmental modifications will be pre-stratified and GMI will be randomised on department level. The program will be evaluated, using 4 arms: (1) GMI and environmental modifications; (2) environmental modifications; (3) GMI; (4) no intervention (control group). Questionnaire data on the primary outcome (need for recovery) and secondary outcomes (daily physical activity, sedentary behaviour, relaxation/detachment, work- and health-related factors) will be gathered at baseline (T0), at 6 months (T1), and at 12 months (T2) follow-up. In addition, an economic and a process evaluation will be performed. Discussion Reducing the need for recovery is hypothesized to be beneficial for employees, employers and society. It is assumed that there will be a reduction in need for recovery after 6 months and 12 months in the intervention group, compared to the control group. Results are expected in 2013. Trial registration Netherlands Trial Register (NTR): NTR2553